Respon tutur siswa autis terhadap tutur direktif guru dalam interaksi pembelajaran di kelas - Robiah, Siti; Ibrahim, Abdul Syukur; Rofi'uddin, AH. (citeus, 2016)
The aim of this study is to describe the form, function and response strategies from autistic studentson the teachers’ directive in the classroom. This study used a case study. The results showed that there are two categories of the students’ spoken responses: (1) speech production in the form of assertive, directive, commissive and expressive; and (2) the speech responses are based on the senses including auditory, visual and emotions. In addition, the function of the students’ responses is categorized into two: (i) the effect of speech production in terms of complaining, agreeing, asking, stating something, thanking, apologizing, asserting, reporting, mentioning and offering; and (ii) the students’ responses as the effect of the teachers’ directive speech acts. Furthermore, the students’ response strategies are divided into two categories, namely: (i) internal and external factors, and (ii) the delivery of the students’ responses